2002
DOI: 10.1073/pnas.242600699
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging reveals retinotopic organization of dorsal V3 in New World owl monkeys

Abstract: Optical imaging of intrinsic responses to visual stimuli in extrastriate cortex of owl monkeys provided evidence for the dorsal half of the third visual area, V3. Visual stimuli were used to selectively activate locations in dorsolateral V2 and the rostrally adjoining presumptive V3. Consistent with the proposed retinotopies of dorsal V2 and dorsal V3, small bars of drifting gratings along the horizontal meridian of the contralateral hemifield activated cortex along the V2͞V3 border, whereas such stimuli along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 49 publications
6
45
0
Order By: Relevance
“…) monkeys, microelectrode recordings from both New World and Old World monkeys have previously demonstrated that a majority of neurons in MT are well tuned for orientation (19)(20)22), although this is not widely recognized. Our data in bush babies also demonstrate that regions surrounding MT, including both the MT crescent and medial superior temporal area, contain cells selective for orientation as reported by others in owl monkeys and macaque monkeys (4,34,35).…”
Section: Visuotopy In Mtsupporting
confidence: 89%
See 1 more Smart Citation
“…) monkeys, microelectrode recordings from both New World and Old World monkeys have previously demonstrated that a majority of neurons in MT are well tuned for orientation (19)(20)22), although this is not widely recognized. Our data in bush babies also demonstrate that regions surrounding MT, including both the MT crescent and medial superior temporal area, contain cells selective for orientation as reported by others in owl monkeys and macaque monkeys (4,34,35).…”
Section: Visuotopy In Mtsupporting
confidence: 89%
“…The three bush babies (greater galagos, now referred to as O. garnetti) used in this study were handled according to an approved protocol from the Vanderbilt University Animal Care and Use Committee. Basic procedures have been described (4). Briefly, bush babies were initially anesthetized with isoflurane (2-4% in O 2 ), and paralysis was induced by i.v.…”
Section: Methodsmentioning
confidence: 99%
“…1 in their commentary), are not found using intrinsic signal imaging. Rather, imaging shows a clear lower field only representation along the outer V2 border with a single horizontal meridian (along the outer border of V2) and a single foveal representation, all consistent with a V3d [9] (for more details, see figs 3 and 4 in the original review [1]). …”
mentioning
confidence: 80%
“…In early studies from our laboratory, we did not recognize V3 and included the territory of V3 in other visual areas (see Kaas and Lyon, 2001). However, now we feel that the issue is largely resolved (Lyon, 2007), as a series of anatomical studies provided strong evidence for V3 (including ventral and dorsal halves) in prosimian galagos (Lyon and Kaas, 2002a) four species of New World monkeys 2002b;Lyon, et al, 2002) and Old World macaque monkeys (Lyon and Kaas, 2002c). V1 and V2 both have connections that associate them with both the dorsal and ventral visual streams, but more of their outputs are directed into the ventral stream (Kaas, 2004a).…”
Section: Cortical Areas Of the Dorsal And Ventral Streamsmentioning
confidence: 99%